Controlling Phalaris minor with novel pyroxasulfone under conservation agriculture in the north-western Indo-Gangetic Plains - KUMAR, SUNIL; KAUR, RAMANJIT (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the winter (rabi) seasons of 2021–22 and 2022–23 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the effectiveness of pyroxasulfone in controlling resistant Phalaris minor within the maize (Zea mays L.)-wheat (Triticum aestivum L.) cropping system. The experiment consisted a split-plot design involving 3 crop establishment systems (Bed + R; ZT + R and CT + R) and 5 weed management strategies, viz. pyroxasulfone (W1); pyroxsulfone fb metsulfuron + carfentrazone (W2); Sulfosulfuron + metsulfuron (W3); UWC (W4); and WFC (W5), replicated thrice. The results from two-year analysis consistently favoured bed planting with residue, which exhibited the lowest P. minor density and total weed population compared to the other two methods with highest weed control efficiency. Among the various weed management options, the combination of pyroxasulfone fb metsulfuron + carfentrazone recorded significantly lowest P. minor density and higher weed control efficiency, similar to the weed-free check. Additionally, this treatment led to significantly higher dry matter accumulation (68.2 g/m2), ear length (12 cm), test weight (41 g) and grain yield (5.8 t/ha) compared to other herbicide treatments, underscoring its outstanding performance.